Clinically relevant preclinical animal models for testing novel cranio‐maxillofacial bone 3D‐printed biomaterials. Issue 2 (15th February 2022) - Hatt, Luan P.; Thompson, Keith; Helms, Jill A.; Stoddart, Martin J.; Armiento, Angela R.
Abstract: Bone tissue engineering is a rapidly developing field with potential for the regeneration of craniomaxillofacial (CMF) bones, with 3D printing being a suitable fabrication tool for patient‐specific implants. The CMF region includes a variety of different bones with distinct functions. The clinical implementation of tissue engineering concepts is currently poor, likely due to multiple reasons including the complexity of the CMF anatomy and biology, and the limited relevance of the currently used preclinical models. The 'recapitulation of a human disease' is a core requisite of preclinical animal models, but this aspect is often neglected, with a vast majority of studies failing to identify the specific clinical indication they are targeting and/or the rationale for choosing one animal model over another. Currently, there are no suitable guidelines that propose the most appropriate animal model to address a specific CMF pathology and no standards are established to test the efficacy of biomaterials or tissue engineered constructs in the CMF field. This review reports the current clinical scenario of CMF reconstruction, then discusses the numerous limitations of currently used preclinical animal models employed for validating 3D‐printed tissue engineered constructs and the need to reduce animal work that does not address a specific clinical question. We will highlight critical research aspects to consider, to pave a clinically driven path for the development of new tissue engineered materials for CMF reconstruction. Abstract : Reconstruction of bone defects of the CMF region is a major and difficult surgical intervention. 3D printing is an ideal biofabrication tool to create patient‐specific tissue engineered bone scaffolds. An appropriate pre‐clinical animal model should be based on the targeted clinical indication. Implementing standardised guidelines for preclinical studies can improve translation.